Determination of five nucleosides by LC‐MS/MS and the application of the method to quantify N6‐methyladenosine level in liver messenger ribonucleic acid of an acetaminophen‐induced hepatotoxicity mouse model. Issue 16 (25th June 2019) - Liu, Ruijuan; Zhao, Fang; Wei, Jingyao; Yu, Pei; Zhang, Ji; Wang, Yueqin; Li, Zeyun; Zhang, Jiali; Zhang, Xiaojian; Tian, Xin
Abstract: Ribonucleic acid N 6 ‐methyladenosine methylation plays an important role in a variety of biological processes and diseases. Acetaminophen‐induced hepatotoxicity is one of the major challenges faced by clinicians. To date, the link between N 6 ‐methyladenosine and acetaminophen‐induced hepatotoxicity has not been studied. In this study, a simple ultra high performance liquid chromatography with tandem mass spectrometry method was developed for the simultaneous determination of five nucleosides (adenosine, uridine, cytidine, guanosine, and N 6 ‐methyladenosine) in messenger ribonucleic acid. After enzymatic digestion of messenger ribonucleic acid, the nucleosides sample was separated on an Acquity UPLC column with gradient elution using methanol and 0.02% formic acid water, and detected by a Qtrap 4500 mass spectrometer with an electrospray ionization mode. The method was validated over the concentration ranges of 4–800 ng/mL for adenosine, uridine, cytidine, and guanosine and 0.1–20 ng/mL for N 6 ‐methyladenosine. It was successfully applied to the determination of N 6 ‐methyladenosine levels in liver messenger ribonucleic acid in an acetaminophen‐induced hepatotoxicity mouse model and a control group. This study offers a method for the determination of nucleoside contents in epigenetic studies and constitutes the first step toward the investigation of ribonucleic acid methylation in acetaminophen‐induced hepatotoxicity, which will facilitate the elucidation of its mechanism.